Investigating Archaeological Cultures Material Culture, Variability, and Transmission - Roberts, Benjamin W.; Vander Linden, Marc.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Since the early 20th century, archaeologists across the world have defined archaeological cultures based on distinct similarities in burials, settlements, technology or objects in space and time. Archaeology has thus many accepted definitions of 'archaeological cultures' but these have all come into question. Yet, archaeological cultures remain the framework for global prehistory.   This volume brings together 17 international case-studies exploring archaeological cultures for regions around the globe and from the Paleolithic to the Bronze Age and beyond. Taking lessons and overarching themes from these studies, the contributors draw important conclusions about cultural transmission, technological innovation, and cultural development.   The result is a comprehensive approach to 'archaeological cultures' addressing specific regions throughout Asia, Europe, North and South America and Africa. This work will be valuable to all archaeologists and cultural anthropologists, particularly those studying material culture.
Historiography -- Culture History in Britain -- Kulturkreislehre: Central European Approach to Culture History -- Cultural History in Russia -- Cultural History in North America -- Culture in the Lower Paleolithic -- Palaeo-cultures, Techno-modes, and techno-facies -- Cultures, Techno-complexes, and Metallurgical Provinces -- Technology and Culture Contact Across Southern Iran -- Creating Communities -- Archaeological Cultures in the Caucasus and Steppe during the Bronze Age -- Cultural Complexity and Bronze Age Institutions -- Culture of Humanity and its Transformation in European Prehistory -- Pottery traditions, Social Affiliation, and Linguistic Groupings in Africa -- Evolutionary Archaeological Definition of Culture -- Prehistoric Archaeological Culture -- Archaeological Cultures and the Spread of the Neolithic in the Near East -- Origins and Early Dispersals of the Austronesian Speaking Peoples -- Material Culture, Agriculture, and Linguistics in Peru during the Middle Horizon Period -- Conclusions and Future Directions.
Keywords: Archaeology; Cultural heritage; Archaeology; Cultural Heritage